FRI0708-HPR The use of technology for symptom measurement in rheumatoid arthritis: a qualitative investigation. (12th June 2018) - Matcham, F.; Williams, R.; Foncel, E.; Tung, H.-Y.; Norton, S.; Galloway, J.; Hotopf, M.
Abstract : Background: Rheumatoid Arthritis (RA) outcome measurement is limited by infrequent appointments, triggered by symptom flares, linking blood test data with retrospective recall of symptoms. Remote measurement technologies (RMT), such as wearable sensors or smartphone apps, provide opportunity for ongoing measurement of symptoms such as pain, fatigue, and depression, which may vary throughout the day, offering new insight into the lived experience of chronic illness [1]. However, implementation of such data collection strategies requires careful development with the service-user an integral part of co-design to maximise real-world acceptability [2]. Objectives: This study aimed to gather qualitative information about service-user priorities for using RMT for symptom measurement. Methods: Two focus groups were conducted in people with RA, using a semi-structured topic guide designed to elicit thoughts about RA symptoms considered important and acceptable for measurement via RMT. The focus groups were moderated by an expert service user (RW) and research lead (FM). A systematic thematic analysis was applied to the data, using a coding framework to extract themes and sub-themes by two researchers independently. Results: A total of 9 participants attended the two focus groups. Participants were aged 23–77 (mean=55.8, SD=18.1), with a mean disease duration of 20.2 (SD=15.2). All 9 were female, with 44.4% identifying as White British. Symptoms prioritisations and the perceived benefits and risks of technology were categorised into several themes including: personal empowerment; communication with healthcare teams; routine/convenience; and under-prioritised symptom experiences. Conclusions: The results of these focus groups highlight several areas to focus RMT development in this area, including identifying the symptoms patients feel are under-prioritised by healthcare providers, and establishing methods to ensure RMT can be embedded in daily activities despite fluctuating symptom severity. Future work testing specific app prototypes and wearable usability can ensure RMT projects are developed with optimised user experience. References: 1. Lee YG, Jeong WS, Yoon G. Smartphone-based mobile health monitoring. Telemedicine and E-Health2012;18:585–90. 2. Grainger R, Townsley H, White B, Langlotz T, Taylor WJ. Apps for people with rheumatoid arthritis to monitor their disease activity: A review of app for best practice and quality. JMIR mHealth and uHealth2017;2:e7. Acknowledgements: We thank Radka Chura for her assistance with recruitment and all participants for their contribution. Disclosure of Interest: None declared